Student Word of Mouth in Higher Education: A Systematic Review of Key Determinants and Implications for Underserved Regions - Raya, Silfanus Lebu; Mulyono, Mulyono; Iswari, Hanif Rani (Bulletin of Management and Business, 2024)
Abstfac student word of mouth (WOM) plays a strategic role in enhancing the reputation and attractiveness of higher education institutions, particularly in regions with limited access to formal information such as Nusa Tenggara Timur (NTT). WOM represents a voluntary form of communication that reflects students’ authentic academic experiences and serves as a credible, cost-effective promotional channel for reaching prospective students. This study aims to identify key factors influencing the formation of WOM in higher education through a Systematic Literature Review (SLR) approach. A total of 52 peer-reviewed articles published between 2020 and 2024 were analyzed thematically. The findings reveal that academic service quality, perceived value, and institutional image are the most dominant determinants of positive student WOM. Academic service quality contributes to student satisfaction, perceived value acts as a cognitive-affective bridge that strengthens students’ intention to recommend their institution, and institutional image reinforces student trust and long-term loyalty. These findings offer practical implications for higher education institutions seeking to expand student recruitment from underserved regions such as NTT. By prioritizing high-quality academic services and fostering strong perceptions of value, institutions can organically stimulate WOM as a sustainable and impactful marketing strategy to attract students from these areas.